Addressing Social Issues and Ensuring Social Security in Vietnam During the Renovation Period - Hien, Do Thi; Thuy, Hoang Thi; Van, Hoang Thi (Journal of Ecohumanism, 2024)
Vietnam's national renovation has gone through four decades. Throughout the comprehensive renovation process, the understanding of the fundamental aspects of social life has become increasingly clear, reflecting the essence of the socialist system that Vietnam has chosen. Social issues encompass all aspects of human life. The level of economic development provides the material conditions to implement social policies, but social goals are the ultimate purpose of economic activities. Even within the framework of economic activities, social policies directly impact labor productivity, product quality, etc., hence the need for basic, long-term social policies that align with the requirements and capabilities during the initial phase of the transitional period. This article focuses on clarifying the views and policies of the Party and the Vietnamese government on addressing social issues and ensuring social security; highlighting both the achievements and limitations in the process of addressing social issues and ensuring social security in Vietnam during the renovation period.